PERLINDUNGAN HUKUM TERHADAP NARAPIDANA WANITA DI LEMBAGA PEMASYARAKATAN WANITA KELAS II A TANJUNG GUSTA MEDAN - Rudolf Silaban; Mhd. Erwin; Otonius Lawolo (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2021)
A convict is someone who is found guilty of his actions, and has obtained a court decision that has permanent legal force. In general, it can also be said that people who have been deprived of their independence and locked up in detention rooms or what are often called Correctional Institutions (Lapas). Prison is a place to carry out coaching for prisoners, including female prisoners. Women are figures who must be protected and must be respected and cared for and considered for the future. The guidance carried out on female prisoners is a form of effort to make the woman a complete human being. In connection with this, the government is obliged to provide legal protection for female prisoners in order to achieve and fulfill their rights in prisons in accordance with applicable laws and regulations. This research uses empirical juridical/sociological methods by using data obtained from legal practice or social phenomena related to this thesis and based on applicable legal norms. The implementation of guidance carried out at the Class II A Women's Correctional Institution in Medan is based on Law Number 12 of 1995 concerning Corrections which explains that only loss of independence is the only thing experienced by prisoners, all of their rights must be fulfilled like humans in general. In Law Number 12 of 1995 concerning Corrections, it further regulates the rights of female prisoners in article 14. In the implementation - the implementation of the rights of women prisoners carried out at the Class II A Medan Women's Prison has been carried out in terms of the coaching process, however in the process, it has been carried out optimally, but in its implementation, obstacles were found so that the process carried out was hampered and there were also things that supported its implementation during the coaching process.